Rapid and Sustained Symptom Relief in Patients With Ulcerative Colitis Treated With Filgotinib: Data From the Phase 2b/3 SELECTION Trial. (23rd August 2022) - Danese, Silvio; Ferrante, Marc; Feagan, Brian G.; Peyrin-Biroulet, Laurent; Hibi, Toshifumi; Sandborn, William J.; Schreiber, Stefan; Ritter, Timothy; Loftus, Edward V.; Rogler, Gerhard; Oortwijn, Alessandra; Yun, Chohee; et al.
Abstract : INTRODUCTION: Patients with ulcerative colitis (UC) regard rapid onset of action among the most important aspects of their treatment. We used the partial Mayo Clinic Score (pMCS) and component patient-reported subscores to assess the rapidity and sustainability of response to filgotinib, a once-daily, oral Janus kinase 1 preferential inhibitor, in adults with moderately to severely active UC in the phase 2b/3 SELECTION trial. The association between early symptomatic improvements and health-related quality of life (HRQoL) outcomes was also assessed. METHODS: In these post hoc analyses of the double-blinded, randomized, placebo-controlled 58-week SELECTION trial (NCT02914522), rectal bleeding and stool frequency diary data on days 1–15 and pMCS remission and response at multiple time points including weeks 10 and 58 were evaluated. HRQoL was assessed using the Inflammatory Bowel Disease Questionnaire at weeks 10 and 58. RESULTS: Filgotinib 200 mg relative to placebo improved rectal bleeding and stool frequency within 7 days ( P < 0.05). By week 2, greater proportions of filgotinib 200 mg-treated patients than placebo-treated patients achieved pMCS remission (biologic-naive, 15.1% vs 8.0%, P = 0.0410; biologic-experienced, 10.3% vs 4.2%, P = 0.0274). A similar treatment effect was observed at week 58 ( P < 0.0001). Day 7 rectal bleeding and stool frequency subscores were associated with the Mayo Clinic Score response at weeks 10 and 58. Patients in pMCS remission at weeks 10 and 58 had greater improvements in the Inflammatory Bowel Disease Questionnaire score than those not in pMCS remission. DISCUSSION: Filgotinib 200 mg daily resulted in rapid and sustained improvements in both UC symptoms and HRQoL.